1977
DOI: 10.1007/bf01869937
|View full text |Cite
|
Sign up to set email alerts
|

Differences between resting and insulin-stimulated amino acid transport in frog skeletal muscle

Abstract: We have compared some features of the resting and the insulin-stimulated uptake of alpha-aminoisobutyrate (AIB) in frog skeletal muscle. We found a substantial difference between the two processes, namely, that resting AIB uptake is Na-independent while the insulin-stimulated fraction of the AIB uptake is Na-dependent. Since the amino acid transport systems in frog skeletal muscle are poorly characterized, we have also surveyed some of their properties. One of the most interesting findings of this survey is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1978
1978
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…It was suggested in that paper that activation of amino-acid transport by insulin was not dependent upon the Na--electrochemical potential difference but rather the consequence of an increased activity or number of membrane transporters. Experiments in vitro with frog skeletal muscle have shown that resting AIB uptake was paradoxically Na § independent, whereas stimulation of AIB transport by 250 mU/ml insulin was dependent upon extracellular sodium [13]. In this study ouabain at 10 -5 M had no inhibitory effect on either resting or insulin-stimulated AIB uptake.…”
Section: Regulation Of Amino-acid Transport By Insulincontrasting
confidence: 46%
“…It was suggested in that paper that activation of amino-acid transport by insulin was not dependent upon the Na--electrochemical potential difference but rather the consequence of an increased activity or number of membrane transporters. Experiments in vitro with frog skeletal muscle have shown that resting AIB uptake was paradoxically Na § independent, whereas stimulation of AIB transport by 250 mU/ml insulin was dependent upon extracellular sodium [13]. In this study ouabain at 10 -5 M had no inhibitory effect on either resting or insulin-stimulated AIB uptake.…”
Section: Regulation Of Amino-acid Transport By Insulincontrasting
confidence: 46%
“…In several tissues the stimulation of amino acid transport has been shown to be independent of protein synthesis, either by an insensitivity to inhibitors or by an induction too rapid to involve de novo protein synthesis. Examples include the insulin effects in mammary tissue [133], diaphragm [121,124], and frog skeletal muscle [134]; the growth hormone-mediated enhancement in diaphragm [123]; a portion of the insulin and glucagon stimulation in rat hepatocytes [135]; and the short-term thyroid effects on System L activity in cartilage tissue [69,136]. Edmondson and Lumeng [135] have shown that glucagon stimulates System A transport in freshly isolated rat hepatocytes without a significant lag period, a result obtained by others with isolated perfused liver [64,99,100,137] and hepatocytes in suspension [65,73], but not with primary cultures of hepatocytes ( [70], Schwass, D.E.…”
Section: Ivf-1 De Novo Synthesis Of Transport Carriersmentioning
confidence: 99%